History of Indonesian Military Role in the Era of Independence Revolution, 1945-1950 - Fatgehipon, Abdul Haris (ASPENSI in Bandung, Indonesia, 2017)
ABSTRACT: The history of Indonesian military formation is interesting to be examined. The Indonesian military was formed after the independence as a part of government structure under the President. The Indonesian military was established out of the various elements of military organization formed by Dutch colonial administration and Japanese occupation in Indonesia. As it was born in the era of independence revolution, it received support from various people paramilitary troops. Although it was autonomously established by itself, the government could oversee it under the supremacy of the civilian government. The research method used in this paper is heuristic, in which to get the primary and secondary data, the author conducted literature, documents, and archives review from several Universities and Research Institutions. The Indonesian military showed its role in maintaining the countrys sovereignty during the Dutch military aggression, first (July 1947) and second (December 1948), carried out by the Dutch colonial government. When President Sukarno and Vice President Mohamad Hatta Â surrendered to the Dutch government and handed over the power to Mr. Syafruddin Prawiranegara, who then he formed PDRI (Pemerintahan Darurat Republik Indonesia or Emergency Government of the Republic of Indonesia), the military leadership gave full support to the PDRI. In the process of political dynamics, finally, the Indonesian military also to be loyal and supported the civil government led by President Sukarno and Vice President Mohamad Hatta.KEY WORDS: Indonesian Military; Time of Revolution; Independence; Diplomacy and Struggle; Social and Political Integration.About the Author: Dr. Abdul Haris Fatgehipon is a Lecturer at the Department of Social Studies Education, Faculty of Social Science UNJ (State University of Jakarta), Gedung K, Kampus UNJ, Jalan Rawamangun, Jakarta, Indonesia. For academic interests, the author is able to be contacted via his e-mail at: pertahanan@yahoo.com Â How to cite this article? Fatgehipon, Abdul Haris. (2017). âHistory of Indonesian Military Role in the Era of Independence Revolution, 1945-1950â in TAWARIKH: International Journal for Historical Studies, Vol.8(2) April, pp.217-228. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Chronicle of the article: Accepted (August 17, 2016); Revised (December 27, 2016); and Published (April 28, 2017).